Tingkat Keterampilan Dribbling Dalam Sepak Bola Di SSB Indrabouma Kabupaten Indramanyu - Mohamad Saepuloh; Mochamad Zakky Mubarok; Fauzan Effendy (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The purpose of this study is to examine the Level of Dribbling Skills in Football at SSB Indrabouma, Indramayu Regency. This research is a quantitative descriptive study using tests and measurements methods. The instrument in this study is a dribbling test with a test validity level of 0.78 and a reliability level of 0.80. The population of this study is SSB Indrabouma, Indramayu Regency. Data analysis uses quantitative descriptive statistics with category norm tables to determine the level of football dribbling skills categorized as very good, good, sufficient, poor, and very poor. The results of this study based on percentages are categorized as 'Very Good' with 3 players at 11.5%, 'Good' with 6 players at 23.1%, 'Sufficient' with 9 players at 34.6%, 'Poor' with 5 players at 19.2%, and in the category 'Very Poor'. as many as 3 players with a percentage of 11.5%.